Acertannin Prevented Dextran Sulfate Sodium-induced Colitis by Inhibiting the Colonic Expression of IL-23 and TNF-α in C57BL/6J Mice - Kimura, Yoshiyuki; Taniguchi, Masahiko; Okuda, Takuo (Planta Medica, 2023)
The present study investigates the effects of acertannin on colitis induced by dextran sulfate sodium (DSS) and changes in the colonic levels of the cytokines interleukin (IL)-1β, IL-6, IL-10, IL-23, tumor necrosis factor (TNF)-α, the chemokine monocyte chemoattractant protein (MCP)-1, and vascular endothelial growth factor (VEGF).We examine the following: inflammatory colitis was induced in mice by 2% DSS drinking water given ad libitum for 7 days. Red blood cell, platelets, and leukocyte counts and hematocrit (Ht), hemoglobin (Hb), and colonic cytokine and chemokine levels were measured. The disease activity index (DAI) was lower in DSS-treated mice orally administered acertannin (30 and 100 mg/kg) than in DSS-treated mice. Acertannin (100 mg/kg) inhibited reductions in the red blood cell count and Hb and Ht levels in DSS-treated mice. Acertannin prevented DDS-induced mucosal membrane ulceration of the colon and significantly inhibited the increased colonic levels of IL-23 and TNF-α. Our findings suggest that acertannin has potential as a treatment for inflammatory bowel disease (IBD).
Keywords: Acer saccharum; Aceraceae; acertannin; inflammatory bowel disease; interleukin-23; tumor necrosis factor-α